Information systems security and privacy : first International Conference, ICISSP 2015, Angers, France, February 9-11, 2015, revised selected papers /: first International Conference, ICISSP 2015, Angers, France, February 9-11, 2015, revised selected papers. (2015) - Unknown
No abstract available